STRATEGI DIGITAL BRANDING DAN PROMOSI UMKM MELALUI INSTAGRAM DAN WEBSITE DI DESA TABA MULAN - Vatresia, Arie; Zarah Juaita, Aisyah Amelia; Ridho, Muhammad Faiz; Armelia, Zaskia Fasha (Dharmakayana, 2025)
This Community Service Program (KKN) carries the theme of digital promotion through the strategic use of two main digital media: Instagram and the Village Website. Instagram is used as a dynamic visual promotion medium for local MSME products, while the village website serves as an information center as well as a village branding tool. The main objectives are to expand the marketing reach of MSME products, improve community digital literacy, and build the professional image of Taba Mulan Village, Kepahiang Regency. The results show that the integration of social media and the village website not only increases local product exposure but also strengthens the village's identity and credibility in the digital space. Keywords: Digital Branding, MSME Promotion, Instagram, Village Website, Digital Literacy, Community Service Program